"They speak 'incorrect' English" understanding Taiwanese laerners' views on L2 varieties of English - Kobayashi, Iori (2008)
This study employed written interviews to understand the views of Taiwanese learners on the second language (L2) varieties of English. The data was collected at a private university language center in the Philippines, where a group of Taiwanese students participated in an English language program. The main findings of the study were the following: (1) Many participants viewed a native speaker variety of English as the sole target model; and (2) They viewed the L2 variety of English they came into contact with in the Philippines as substitute for that target model. The result of the study calls for heightened awareness among Taiwanese learners regarding the widespread use of English as an international language and increased exposure to L2 varieties of English.
Includes bibliographical references (page 94).